Diesel degradation by residual substrate of Agaricus bisporus at the microcosm level - Mauricio-Gutiérrez, Amparo; Jiménez-Salgado, Teresita; Tapia-Hernández, Armando; Romero-Arenas, Omar (Revista Mexicana de Ciencias Agrícolas, 2022)
In Mexico there are large areas of soils contaminated by hydrocarbons, causing economic and social damage to agricultural production, in this sense, the need to seek economic alternatives that allow contributing to the recovery of affected agricultural soils arises. The present work aimed to determine the biodegradation of diesel in an agricultural soil using residual substrates (RS) of Agaricus bisporus. Soil contaminated with 7 039 ppm of diesel was used with different doses of RS, incubated for 28 days at 37 ºC. CO2 production, diesel biodegradation, initial and final population of fungi, as well as specific enzymatic activity of initial and final laccases were determined. In all treatments, removal increased significantly (p= 0.001) at 37 °C, as well as CO2 production rates. Treatment T4 had the highest percentage of diesel biodegradation (68.747%) and a final cumulative production of 6.144 x 10-4 mmol CO2 m-3. The activity of laccases and tolerant fungal populations decreased in all treatments; in addition, the bacteria increased from 7.6 to 8.9 log CFU gss-1. Therefore, the diesel biodegradation activity is attributed to bioaugmentation and biostimulation by the residual substrate of A. bisporus.
Keywords: bioaugmentation; biodegradation; biostimulation; enzymatic activity